2014
DOI: 10.1186/1475-9276-13-24
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in public health care delivery in Zambia

Abstract: BackgroundAccess to adequate health services that is of acceptable quality is important in the move towards universal health coverage. However, previous studies have revealed inequities in health care utilisation in the favour of the rich. Further, those with the greatest need for health services are not getting a fair share. In Zambia, though equity in access is extolled in government documents, there is evidence suggesting that those needing health services are not receiving their fair share. This study seek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Garcia-Subirats et al 26 found similar results, that is, socioeconomic differences in resolution of health problems and initial health care-seeking in a large city in Brazil. Previous studies 4,28,35 showed that use of the private sector was more frequent among higher socioeconomic groups. Santos et al 36 found some inequalities in health care services favoring the population with private health plans in Brazil.…”
Section: Access Use and Quality Of Health Care Services And Trends mentioning
confidence: 81%
“…Garcia-Subirats et al 26 found similar results, that is, socioeconomic differences in resolution of health problems and initial health care-seeking in a large city in Brazil. Previous studies 4,28,35 showed that use of the private sector was more frequent among higher socioeconomic groups. Santos et al 36 found some inequalities in health care services favoring the population with private health plans in Brazil.…”
Section: Access Use and Quality Of Health Care Services And Trends mentioning
confidence: 81%
“…These pro-rich characteristics can easily access combine both facilities, primary health care and hospital visit, which make wider inequity significantly. 27 Reflecting this result, young individuals with sufficient financial conditions have to be encouraged to be participants of Indonesia NHI than to purchase private health insurance. In the early stages, BPJS Kesehatan should appeal to those characteristics at manager level and higher to be encouraged to be NHI program participants.…”
Section: Discussionmentioning
confidence: 99%
“…The production, recruitment and retention of human resources play a critical role in the success of the decentralization. In the current study in Zambia, staff was not well oriented and change management was not actively pursued prior to realignmentespecially pertaining to role allocation, responsibilities and management as has been recommended (Central Statistical Office Zambia;2014). Unfortunately these country experiences have not been widely shared (Bossert et al, 2003).…”
Section: Discussionmentioning
confidence: 91%
“…As the health sector in Zambia thrives to deepen decentralization including transfer pf responsibility of service provision to the Ministry of Local Government, there is need for adequate preparation focusing on systems and structures as well as the human resource factor including change management approach. This human resource software requires a paradigm shift with need to target the WHO benchmarks on the basic minimum 23/10000 health workers per population (right now we have less than 8) to attain UHC (Central Statistical Office Zambia;2014) to enable the requisite continuum of interventions across the district community divide to ensure the community is fully engaged and empowered. The dysfunctional status of the community health strategy in the Zambia setting is a major cause of disjointedness of the continuum of care between community and health facility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation